Adaptation, acceptability and feasibility of Problem Management Plus (PM+) intervention to promote the mental health of young people living with HIV in Kenya: formative mixed-methods research. Issue 5 (24th September 2022) - Nyongesa, Moses Kachama; Mwangome, Eva; Mwangi, Paul; Nasambu, Carophine; Mbuthia, Judy Wanjiru; Koot, Hans M.; Cuijpers, Pim; Newton, Charles R. J. C.; Abubakar, Amina
Abstract : Background: Problem Management Plus (PM+) is a psychological intervention that seeks to address common mental disorders among individuals exposed to adversity. Thus far, the potential for delivering PM+ by mobile phones has not been evaluated. Aims: To adapt PM+ for telephone delivery (ten weekly sessions of about 45 min each) and preliminarily evaluate its acceptability and feasibility with young people living with HIV (YLWH) in coastal Kenya. Method: This was a mixed-method formative research. Qualitative data collection included consultations with stakeholders, conducting key informant interviews with HIV care providers and focus group discussions with potential end-users, i.e. YLWH. Moreover, brief exit interviews with recipients of the adapted PM+ were conducted. Quantitative acceptability and feasibility indicators and outcome measures were tracked/assessed during PM+ preliminary implementation involving 70 YLWH. Results: From the qualitative inquiries, the adapted PM+ emerged as contextually appropriate, acceptable and feasible for mobile phone delivery, despite some concerns around missing nonverbal cues and poor network connectivity. High recruitment (85%) and fair programme retention (69%) were observed. Intervention sessions over the telephone lasted 46 min on average (range 42–55 min). Preliminary feasibility data indicated that the adapted PM+ has the potential of reducing common mental disorders among YLWH from the Kenyan coast. Conclusions: PM+ is acceptable and can feasibly be delivered via mobile phone to YLWH in coastal Kenya. This study sets the stage for a future fully powered, randomised controlled trial assessing the efficacy of the adapted PM+ in this or a similar setting.